2014
DOI: 10.1167/iovs.14-14093
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pro-Angiogenic Function for Interferon-γ–Secreting Natural Killer Cells

Abstract: A novel pro-angiogenic function for interferon-c-secreting natural killer cells. Invest Ophthalmol Vis Sci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…We show for the first time that alloreactive host T cells promote angiogenesis after transplantation, largely through expression of VEGF-A. Accordingly, we propose that the angiogenic process following corneal transplantation develops in 2 phases: an early phase related to the postoperative healing process mediated by innate immune cells, as described elsewhere, 5658 and a late phase mediated by alloreactive T cells responsible for graft rejection.…”
Section: Discussionsupporting
confidence: 64%
“…We show for the first time that alloreactive host T cells promote angiogenesis after transplantation, largely through expression of VEGF-A. Accordingly, we propose that the angiogenic process following corneal transplantation develops in 2 phases: an early phase related to the postoperative healing process mediated by innate immune cells, as described elsewhere, 5658 and a late phase mediated by alloreactive T cells responsible for graft rejection.…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, we showed that when the epithelium is challenged with flagellin, CXCL10 was expressed in the basal epithelial cells and a group of CXCX3 positive cells were seen lining as a single layer underneath the epithelial layer in the stroma; these cells were shown to be natural killer (NK) cells [32]. NK cells have been shown to possess pro-angiogenic property in non-small cell lung cancer [48], to remodel maternal vasculature in early pregnancy [49], and to induce angio-genesis by promoting enhanced VEGF expression by macrophages in the cornea micropocket assays and the laser-induced choroidal neovascularization mouse models (C57BL/6) [50]. It is, however, unclear if the pro-angiogenic effects are related to inflammation mediated by NK cells which are known to be a major source of interferon-γ [50].…”
Section: Discussionmentioning
confidence: 99%
“…NK cells have been shown to possess pro-angiogenic property in non-small cell lung cancer [48], to remodel maternal vasculature in early pregnancy [49], and to induce angio-genesis by promoting enhanced VEGF expression by macrophages in the cornea micropocket assays and the laser-induced choroidal neovascularization mouse models (C57BL/6) [50]. It is, however, unclear if the pro-angiogenic effects are related to inflammation mediated by NK cells which are known to be a major source of interferon-γ [50]. Since our data indicates that epithelial expression of CXCL10 is anti-angiogenic, it is likely that CXCL10, in addition to being a chemokine, may directly act on both hem-and lymph-endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis and blood vessel remodeling are vital steps in metastatic processes, and several research studies reported that IFN‐γ‐secreting NK cells function in favor of them . Similarly, melanoma cells aggressiveness can be increased via NK cells and also it might favor these cells to shift from proliferative to invasive forms through inducing stemless upregulation or typical markers of epithelial‐mesenchymal transition (EMT).…”
Section: The Factors and Mechanisms By Which Ilcs Enhance Tumor Progrmentioning
confidence: 99%